PROSES PENEMUAN HUKUM - Putra Halomoan Hsb (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
Legal discovery, in essence embody scientifically pengembanan law and praktikal.Penemuan law as a reaction to situations presented problematikal people in terms of the law with respect to the legal questions (rechtsevragen), conflicts of law or legal disputes .Penemuan law with respect to finding a solution-settlement and answers based hokum.sistem rules of law are two main legal systems which are widely applied in the world, but on the other two legal systems there are some other law that is applied in the world of legal system Islam (Islamic law) and the communist legal system (communist law) .In general, the direction and goals of the political establishment of the law have been recorded in 1945 and has been clearly formulated by the founders of the nation, from the opening to the trunk. The new constitution, it is also clear mention of the authorized body in the formation of the law, namely the Parliament with legislative functions, the Government (President), and DPD in the problems' daerah'.Politik formation of national law in the future should be more consistent with the objectives that have been outlined by the founding fathers of this nation. Political alignments current national laws should be more emphasis on how to achieve the ideals of the nation enshrined in the 1945 Constitution Political establishment of democratic law and responsive certainly have grown in the noble values of society